Response of preantral follicles exposed to quinoxaline: A new compound with anticancer potential. (February 2020) - Guerreiro, Denise Damasceno; de Lima, Laritza Ferreira; de Sá, Naíza Arcângela Ribeiro; Mbemya, Gildas Tetaping; Ferreira, Anna Clara Accioly; Alves, Benner Geraldo; Sant'anna Maranhão, Sarah; do Ó Pessoa, Cláudia; Pinheiro, Alessandra Campbell; Nogueira, Thais Cristina Mendonça; de Souza, Marcus Vinícius Nora; de Figueiredo, José Ricardo; et al.
Abstract: The culture of preantral follicles as an in vitro model to evaluate the toxicity of new anticancer drug has being established. Therefore, the aim of this study was to evaluate the effect of quinoxaline derivative the 2 2- (XYZC 6H 3 –CH=N-NH)-quinoxaline, 1 (QX) on caprine preantral follicles. We evaluate the follicular morphology and activation, proliferation and apoptosis of granulosa cells and finally the protein (ABCB1) and genes expression (cyclin/Cdks), respectively involved in multidrug resistance and cell cycle progression. Ovarian fragments containing primordial and developing follicles were exposed ( in vitro culture) to different concentrations of QX (QX1.5, QX3.0 or QX6.0 μM/mL) during 6 days. To evaluate the effect of QX, the ovarian tissue was exposed to Paclitaxel 0.1 μg/mL (PTX – negative control) or in culture media without QX (MEM). At the end of exposure time, we realized that the QX (all concentrations) increased ( P < .05) the normal morphology of preantral follicles compared to control (not treated ovarian tissue) or MEM. However, QX6.0 showed a enhanced (P < .05) on follicular activation ( burnout ) and apoptosis than QX1.5 and QX3.0. Expression of ABCB1 was similar between QX1.5 and QX6.0 and both were lower than control, MEM and PTX. Interestingly, the apoptosis rate in QX3.0 was similar to control and MEM and lower then QX1.5; QX6.0 and PTX. We conclude that quinoxaline may be a promising chemotherapeutic agent, however, other concentrations within a defined range (2–5.5 μM) could be widely investigated. Highlights: Quinoxaline (QX6.0) can cause follicular burnout in a more evident and intense way. Quinoxaline at the lowest (1.5 μM) and at the highest (6.0 μM) concentration, seem to inhibit the expression of ABCB1.